2012
DOI: 10.1007/s10815-012-9800-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of ACE I/D, AGT M235T gene polymorphisms with pregnancy induced hypertension in Chinese population: a meta-analysis

Abstract: Purpose There have been many studies concerning the associations of angiotensin-converting enzyme (ACE) I/D, angiotensinogen (AGT) M235T polymorphisms with pregnancy induced hypertension (PIH) among Chinese populations. However, the results were inconsistent, prompting the necessity of meta-analysis. Methods Studies published in English and Chinese were mainly searched in EMbase, PubMed and CBM up to January 2012. Results Twenty-three studies with 3,551 subjects for ACE I/D and seven studies with 1,296 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
(25 reference statements)
1
15
0
1
Order By: Relevance
“…Epidemiological studies show that various genetic and environmental factors are involved in the pathogenesis of Hypertension. ACE is the key enzyme in the Renin-Angiotensin system, which can catalyze the conversion of Angiotensin-I to Angiotensin-II [22,24,41].The ACE gene is located in chromosome 17q23 and contains 26 exons and 25 introns with a total length of 21 kb. The Insertion/Deletion (I/D) polymorphisms are defined according to presence or absence of the 287 bp fragment in intron 16.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies show that various genetic and environmental factors are involved in the pathogenesis of Hypertension. ACE is the key enzyme in the Renin-Angiotensin system, which can catalyze the conversion of Angiotensin-I to Angiotensin-II [22,24,41].The ACE gene is located in chromosome 17q23 and contains 26 exons and 25 introns with a total length of 21 kb. The Insertion/Deletion (I/D) polymorphisms are defined according to presence or absence of the 287 bp fragment in intron 16.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Zhu et al 15. found that ACE I/D was significantly associated with PIH in Chinese populations, but no significant association was found between ACE I/D and PIH in the subgroup with large number of cases (>100 cases).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis8 that included 27 studies showed that AGT rs699 was significantly associated with PE (OR = 1.26, 99% CI: 1.00, 1.59), but the included studies had high heterogeneity (I 2  = 70%). Another meta-analysis15 investigated the association between AGT rs699 and PIH in Chinese population and found significant associations in dominant genetic model, recessive genetic model, and allelic model. Although it is widely accepted that GH and PE should be analyzed separately for their different genetic backgrounds16, most gene-association studies performed in China have not differentiated between the two diseases; therefore, meta-analyses could not separately pool the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,[37][38][39] A large study (more than 1000 Caucasian women) conducted by Pfab with coworkers did not reveal the association of I/D polymorphism of the ACE gene with BP level during a pregnancy. 40 Meantime, a meta-analysis of more than 50 studies showed a significant association of the I/D polymorphism with PIH and preeclampsia in Chinese, 41,42 and in Asians and Caucasians. 43 The observed inconsistency in the above results may be explained by inter-population and interethnic differences in the distribution of the I/D polymorphism: allele D is predominant in Caucasians from Europe, Australia and the USA, whereas allele I is more prevalent among Chinese and Indians.…”
Section: Discussionmentioning
confidence: 99%